Parastasia dreviflagellata sp. n. — новый род эвгленоидид (Protozoa, Euglenoididae) из кишечника циклопа Eucyclops serrulatus - Палиенко, Л.П. (Вестник зоологии, 1982)
An illustrated description of a new parasitic euglenoidid species- Parastasia brevillagellata sp. nov. from Eucyclops serrulatus intestine is given. Type locality- Kiev vicinity. From other congeneric species it differs by shortened flagellum at reproductive stage- two times shorter than the cell length (in other species almost equal) as well as by some other characters.